Combination of entecavir with thymosin alpha-1 in HBV-related compensated cirrhosis: a prospective multicenter randomized open-label study. (31st May 2018) - Wu, Xiaoning; Shi, Yiwen; Zhou, Jialing; Sun, Yameng; Piao, Hongxin; Jiang, Wei; Ma, Anlin; Chen, Yongpeng; Xu, Mingyi; Xie, Wen; Cheng, Jun; Xie, Shibin; et al.
ABSTRACT: Background : Thymosin alpha-1 (Ta-1) suppresses HBV viral replication, while the evidence of combination effect with nucleoide is still limited. We aimed to investigate the efficacy and safety of combination therapy of Ta-1 with entecavir (ETV) in patients with compensated liver cirrhosis. Research design and methods : A total of 690 patients were randomized to receive Ta-1 plus ETV (n = 351) or ETV monotherapy (n = 339) for 52 weeks after 26 weeks of ETV treatment, followed by continued entecavir therapy. The primary endpoint was defined as liver decompensation, hepatocellular carcinoma (HCC) or death. Results : The median followed up was 38.2 months. The cumulative incidence of liver decompensation, HCC, or death were similar between two groups. During the Ta-1 combination treatment, the HCC incidence was 1.7% in combination group and 2.1% in ETV group, without new HCC cases developed during week 39 to week 77 in combination group. The virologic response, serologic response, biochemical response was similar between two groups at week 104. Both therapies were well-tolerated. Conclusion : There was no significant difference between two groups in endpoint events, while combination therapy with Ta-1 has a tendency to inhibit the development of HCC.